Do wages reflect labor productivity? The case of Belgian regions - Jozef Konings; Luca Marcolin (IZA Journal of European Labor Studies, 2014)
We simultaneously estimate a wage and a labor productivity equation where we include regional dummies as explanatory variables. We find that the wage-productivity gap reached 11% for Brussels and 4.2% for Wallonia in the years 2005 - 2012. This was driven by the negative performance in labor productivity of firms in these regions relative to Flanders, which more than compensated for the advantage in average salary cost they enjoyed. These results are coherent with the existence at the regional level of institutional barriers to the firm-level adjustment of wages to labor productivity.
Keywords: J24; J31; J5; R23; 330